INFLUENCIA DE DISTINTOS TRATAMIENTOS CULTURALES EN UNA FORESTACIÓN CON ENCINAS EN AMBIENTE SEMIÁRIDO - Jiménez, M N; Ripoll, M A; Navarro, F B; Gallego, E; De Simón, E (IV Congreso Forestal Español, 2005)
En este trabajo se analizó el efecto que produjeron distintos tratamientos culturales (binas, aplicación de mulches y riegos en distintas épocas del verano) en una forestación con encinas en un terreno agrícola abandonado, situado en el Altiplano del Conejo (Guadix, SE España), localidad donde la encina tiene un límite de distribución natural por excesiva xericidad. Tras cuatro años de seguimiento (2001-2004), todos los tratamientos excepto el aporte de residuos sólidos urbanos presentaron mayor supervivencia y superficie foliar respecto a la parcela testigo. Los mejores resultados se obtuvieron en la parcela que recibió riego estival continuo. Sin embargo, altura y diámetro no mejoraron significativamente con los tratamientos, tan sólo en el caso de riegos continuados. Palabras
Keywords: binas; mulches; quercus ilex subsp. ballota; Riegos; terreno abandonado

Modificación del microclima edáfico producido por riegos en forestaciones de zonas semiáridas - Jiménez, M N; Ripoll, M A; Navarro, F B (Investigación agraria. Sistemas y recursos forestales, 2004)
In this work, we analyse the effect that the irrigation carried out in different times during the summer drought produces on the edaphic microclimate over holm oak plants (Quercus rotundifolia) in abandoned agricultural soils of continental semiarid climate. The study has been done over 5 plots of 60 plants each, located in the high plateaux of Rambla Becerra (Guadix-Granada), in which it has been accomplished a continuation of the survival rate and development after the planting during two years (2001-2002). The answer of the plant to its new medium was excellent in all the irrigated plots, whereas in the witness plot (without irrigation) the survival is considerably inferior. The height of the holm oaks in those plots with any kind of irrigation is significantly superior than the ones in the witness plot, and the diameter of the holm oaks of the plots which receive continuous summer irrigation shows significant differences with respect to the rest of the plots. The bioclimatic diagrams achieved in each plot reflect relevant differences; the summer irrigation reaches to reduce the drought period and even, in the plot that receives the continuous summer irrigation, this is eradicated, thus generating a new period of vegetation activity. The humidity of the soil shows significant differences, being the plot number 8, which is continually being irrigated, the only one that keeps the humidity in depth. The hydric deficit diminishes punctually in the plots irrigated only once, whereas in the parcel n. 8 diminishes drastically with the following increase in the vegetation activity.
Keywords: agricultural; bioclimatic diagrams; humidity; microclimate; Soil